Long-term sorption of lincomycin to biochars: The intertwined roles of pore diffusion and dissolved organic carbon. (15th September 2019) - Liu, Cheng-Hua; Chuang, Ya-Hui; Li, Hui; Boyd, Stephen A.; Teppen, Brian J.; Gonzalez, Javier M.; Johnston, Cliff T.; Lehmann, Johannes; Zhang, Wei
Abstract: Sequestration of anthropogenic antibiotics by biochars from waters may be a promising strategy to minimize environmental and human health risks of antibiotic resistance. This study investigated the long-term sequestration of lincomycin by 17 slow-pyrolysis biochars using batch sorption experiments during 365 days. Sorption kinetics were well fitted to the Weber-Morris intraparticle diffusion model for all tested biochars with the intraparticle diffusion rate constant ( k id ) of 25.3–166 μg g −1 day −0.5 and intercept constant ( C id ) of 39.0–339 μg g −1, suggesting that the sorption kinetics were controlled by fast initial sorption and slow pore diffusion. The quasi-equilibrium sorption isotherms became more nonlinear with increasing equilibration time at 1, 7, 30, and 365 days, likely due to increasing abundance of heterogeneous sorption sites in biochars over time. Intriguingly, low-temperature (300 °C) and high-temperature (600 °C) biochars had faster sorption kinetics than intermediate-temperature (400–500 °C) biochars at the long term, which was attributed to greater specific surface area and pore volume of high-temperature biochars and the substantial and continuous release of dissolved organic carbon (DOC) from low-temperature biochars, respectively. DOC release enhanced lincomycin sorption by decreasing biochar particle size and/or increasing the accessibility of sorption sites and pores initially blocked by DOC. Additionally, a large fraction (>75%) of sorbed lincomycin in biochars after a 240-day equilibration could not be extracted by the acetonitrile/methanol extractant. The strong sorption and low extraction recovery demonstrated the great potential of biochars as soil amendments for long-term sequestration of antibiotics in-situ. Graphical abstract: Image 1 Highlights: Lincomycin sorption to biochars was controlled by pore diffusion in the long term. Quasi-equilibrium sorption isotherms of lincomycin became more nonlinear over time. Release of dissolved organic carbon from biochars enhanced lincomycin sorption. Lincomycin sequestered in biochar pores was highly resistant to extraction.